Pemanfaatan Daun Salam (Syzygium Polyanthum Walp) Dalam Pengendalian Rayap - Syamsudin S; Khaer, Ain; Waru, Andi Khaerunnisa Tenrya (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2023)
Termites are one of insects that belong to the order Isoptera with 3 types of castes, namely the worker caste termites, the soldier caste termites, and the reproductive caste termites. Termites can be found in various ecosystems such as plantations or settlements, especially since the area is an area with climatic conditions that support its breeding, such as in Indonesia. Termites can live on the ground or in wood, especially wood containing cellulose. Bay leaf is a plant with a scientific name (Eugenia Polyantha W.) that contains several compounds, one of which is an essential oil that is volatile and is in the form of a liquid that is capable of killing termites by damaging the respiratory system and reducing the appetite of termites. The purpose of this study was to find out the benefits of boiling water from bay leaves (Syzygium Polyanthum Walp) as a natural pesticide in killing termites. The type of research used is quasi-experimental using the spray method. The samples in this study were 20 termites that were exposed to boiling water of bay leaves with concentrations of 40%, 45%, and 50% and controls whose mortality was counted every 40 minutes for 120 minutes for 3 treatments. The results showed that the average percentage of termite mortality using boiled bay leaf water at a concentration of 50% was 17 individuals (85%), at a concentration of 45% as many as 13 individuals (65%), at a concentration of 40% as many as 5 individuals (25%), and in the control, there was no termite death or without giving bay leaf boiled water. Based on the research results, boiled bay leaves can kill termites. The conclusion of this study, water boiled bay leaves at a concentration of 40% and 45% cannot be said to be able to kill termites and 50% can be said to be able to kill termites with a mortality rate of 85%. Suggestions from this study are that bay leaf cooking water can be used as a vegetable insecticide that can be applied by the community using a concentration or dose of 50% of bay leaf cooking water.